Security and trust management : 12th International Workshop, STM 2016, Heraklion, Crete, Greece, September 26-27, 2016, Proceedings /: 12th International Workshop, STM 2016, Heraklion, Crete, Greece, September 26-27, 2016, Proceedings. (2016) - Unknown
No abstract available